Practically aspects of use of the thermoplasticized gutta-percha in daily endodontichesky practice (Эндодонтия Today)
Article is devoted to clinical aspects of application in daily practice of the dentist of hot gutta-percha on the carrier. The analysis of features of application of this technique in comparison with a method of a lateral compactions of gutta-percha is carried out. At a preclinical stage carried out comparison of apically permeability of the fangs which have been sealed up with application of these techniques. In clinic within 3 years treatment of complications of caries of 878 teeth at 645 patients aged from 18 till 75 years was carried out. During research lack of reliable distinctions in efficiency of application of these techniques is established.